THE USE OF “KOUASS WARE” DURING THE REPUBLICAN PERIOD IN THE ALGARVE (PORTUGAL) - de Sousa, Elisa (Rei Cretariae Romanae Fautorum Acta, 2024)
“Kouass ware” is a type of pottery characteristic of the south of the Iberian Peninsula and the north coast of Morocco. It basically consists in a Hellenistic production, distinguishable especially by the large variation of the colour of its poor quality glaze which varies from red to black. This variation can be seen sometimes at the same vessel.